Development of contextual brochures in learning mathematics to improve student learning outcomes and creativity - Sirojudin Wahid; Nely Naelatul Izza (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2022)
This study aims to produce brochure teaching materials for contextual-based mathematics learning. After the brochure is applied in learning, it will be analyzed whether it can improve mathematics learning outcomes and students' creativity. This study is development research, using 4D development design (define, design, develop, disseminate). The development test was conducted at SMP Assuniyah Losari, involving 52 students. 26 students of class VII A as the control class and 26 students of class VII C as the experimental class. The data collection instruments used in this study were interviews, questionnaires and tests. The results of this study are: (1) producing a mathematics learning brochure with a contextual approach through a 4D development design, (2) a contextual mathematics learning brochure obtaining a score of 0.94 based on the assessment of material experts with high validity criteria, and getting a score of 0.86 based on an expert assessment. media with high validity criteria, (3) the results of data processing on student learning outcomes and creativity using SPSS version 25.0, showed a difference between the control and experimental classes. the use of contextual-based mathematics learning brochures is proven to significantly improve student learning outcomes and creativity. Student responses also showed positive results with a cumulative percentage of 78%